2018
DOI: 10.1007/s10654-018-0368-x
|View full text |Cite
|
Sign up to set email alerts
|

Night shift work and breast cancer: a pooled analysis of population-based case–control studies with complete work history

Abstract: Night shift work has been suspected to increase breast cancer risk but epidemiological studies have been inconsistent due to heterogeneous assessment of exposure to night work. To overcome this limitation, we pooled data of five population-based case-control studies from Australia, Canada, France, Germany, and Spain into a single harmonized dataset using a common definition of night work including 6093 breast cancer cases and 6933 population controls. The odds ratio for breast cancer in women who ever worked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
6
8

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 34 publications
6
110
6
8
Order By: Relevance
“…A recent large pooled analysis on breast cancer that examined also time-related variables showed that risk in premenopausal women was highest in those with current or recent (2 years) night shift work, decreased in women who had left night shift work 2-20 years earlier, and was lowest at 20 years or more since last night shift work. 1 A similar pattern was observed in a large cohort study in the UK 2 that overall did not find any association between breast cancer and night shift in older women, but reported a 10% increase the first 10 years after exposure while a decrease in risk was observed following that period. A relatively similar pattern although not entirely consistent was described for night shift and CLL.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…A recent large pooled analysis on breast cancer that examined also time-related variables showed that risk in premenopausal women was highest in those with current or recent (2 years) night shift work, decreased in women who had left night shift work 2-20 years earlier, and was lowest at 20 years or more since last night shift work. 1 A similar pattern was observed in a large cohort study in the UK 2 that overall did not find any association between breast cancer and night shift in older women, but reported a 10% increase the first 10 years after exposure while a decrease in risk was observed following that period. A relatively similar pattern although not entirely consistent was described for night shift and CLL.…”
supporting
confidence: 79%
“…Beatriz Pérez-Gómez Javier Burgos Inés Gómez-Acebo Javier Llorca Rosana Peiró Jose J. Jimenez-Moleón Juan Alguacil 1 Adjusted for age, education and centre. 2 Adjusted for age, education, centre and lifetime cumulative years of night work.…”
Section: Yours Sincerely Manolis Kogevinas Ana Espinosa Kyriaki Papanmentioning
confidence: 99%
“…Our exposure definition included rotating night shift work schedules with at least 3 nights per month and we assessed cumulative night shift work duration in years. However, recent evidence suggests that other exposure metrics such as shift work frequency (nights/month or number of consecutive nights) and length (hours/day) may also predict breast cancer risk in addition to cumulative lifetime duration (years) 30 . Our study lacked information on shift work frequency and length but these metrics should be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The recent Million Women Study (8), which found no association between shift work and cancer, included subjects of very advanced age. Starting follow-up at an older age may have resulted in the inclusion of more participants less susceptible to the effects of night shift work (7,9). Furthermore, old age is associated with the accumulation of competing risk factors, diminishing the relative role of shift work compared to the other factors (10).…”
Section: Selection Biasmentioning
confidence: 99%
“…Some light is seen in the acknowledgement of the need for better exposure assessment of shift work. The new case-control studies of shift work and breast cancer used interviews to get more precise and relevant information on exposure to night and shift work (7). However, the use of electronic records of working hours would be most optimal.…”
Section: Confounding and Effect Mediatorsmentioning
confidence: 99%